The Change in Physical Properties of Bi2Ca2Co2O8 Thermoelectric Materials Induced by Pb and Rare-Earth Dopings - Inge Magdalena Sutjahja (Institut Teknologi Bandung, 2011)
We report in this paper the change in the physical properties due to dopant effect in Bi2Sr2Co2O8 parent compound system. The doped samples consists of Pb-doped samples (Bi2Sr2Co2O8, x = 0, 0.5, 1.0, 1.5, and 2.0) and RE-doped samples (Bi2-xPbxCa1.9RE0.1Co2O8, RE = Y, La, Pr, Sm, Eu, Gd, and Ho). The structure of this layered oxide system consist of an alternate stack of CoO2 layer and Bi2Sr2O4 block along the c-axis with misfit structure along b-direction. From the analysis of XRD data it is found that the c-axis parameter reduced significantly in the RE-doped samples compared with those of Pb-doped samples, while the value of misfit degree almost the same. The changes in these lattice structures are accompanied by variation in the spin-state of Co-ions and electrical conductivity. We argue that these structural changes and its effect on the electrical transport properties as well as control of the magnetism plays a pivotal role in determining the thermopower in this class of magnetic thermoelectric materials through the entropy of the charge carriers. This, in turn, will determine the thermoelectric performance for application.